(untitled) (International Journal of Engineering and Computer Science, 2015)
Monitoring the environment, capturing significant events, and interpreting physical space information with sensors are increasingly demanded in several application fields such as disaster prevention and recovery, surveillance, home automation, healthcare, structure and machine diagnosis, advanced traceability systems. This project focuses on developing a data acquisition from one place to another place using Zigbee wireless sensor network. For environmental monitoring we are using Temperature sensor and LDR or light sensor to continuously calculating the temperature and light density values in the environment. We are using MEMS sensor to detect abnormal behaviors exhibited by machines for diagnosis purpose and to warn others on the environment so as to prevent accidents from happening. Each owner has their own RFID reader to access information from the environment. If any changes occurred in MEMS, temperature and LDR we can alert the people by using buzzer indication and also LED. Each and every monitoring value can be stored in the memory card for further action. Whenever the particular authorized person show his/her card to the RFID reader the monitored values can be send to the receiver and displayed on LCD. Data acquisition can be possible using Zigbee network. Here we can monitor the sensor network using low power supply or battery. For indicating purpose we are using buzzer and LED whenever in abnormal condition.